Policies and strategies in food and healthy lifestyles - Jesus, s. (2021)
AIM: The rapid growth in industrialisation, urbanisation and market globalisation had a significant impact on population diets and lifestyles. At the same time, the living standards improved, the food availability expanded and became more diversified. However, it occurred an increase in dietary patterns and physical inactivity, which led to a rise in the chronic non-communicable diseases(NCDs), including obesity, diabetes, cardiovascular disease, hypertension, stroke and cancer. It was determined that in 2001 chronic burden diseases contributed 46% in the world and that in 2020 will increase to 57%. So, the present study aimed to analyse the strategies and policies in health and food lifestyles in Europe. The study was developed in the project “A Quadruple Helix Atlantic Area Healthy Food Ecosystem for Growth of SME’s”(AHFES). This project aims to improve the competitiveness and growth of SMEs in the value chain of healthy eating and lifestyles, contributing to the development of a transnational innovation ecosystem that helps entities to access information, partners and markets and align their products and services to the needs and expectations of the European consumer/community. MATERIAL AND METHODS: In the present study was used different approaches and tools. It was made a literature review with the terms of “healthy food policies”, “healthy lifestyles policies” and “food policy”. Another approach was the information collected from the partners about the existing regional policies and strategies in healthy food, where it was made some questions about healthy food and lifestyles and innovation policies, innovation tools and existing support structures and reforms in each country (Portugal, Spain, Ireland, France and the United Kingdom). RESULTS: The countries increasing the policies and measures to be implemented in the area of health. It was found that although most countries have very similar national plans, their policies and levels of implementation vary between them. In general, the implemented measures and policies are organized into two groups: health and lifestyles programmes and policies and support structures and reforms. These groups have high relevance in changing dietary patterns and lifestyles. Besides, in most countries, there was a consensus on the most important and priority age groups for a more effective outcome of measures and policies in the future. These two age groups were children, who are still open to new knowledge and knowledge in the area of food, and the elderly who corresponds to a group that requires the effects of NCD risk factors to be controlled. The measures and policies applied to increase and encourage society to modify its diet and lifestyle were diverse and can be grouped into five groups: nutrition and diet counselling, portion size control, regulation of marketing to children, reformulation and dietary guidelines. CONCLUSIONS: To improve healthy food and lifestyles of the population, it is necessary to regularly re-evaluate strategies and consequent effects on the health status of the community. Besides, to the implementation of strategies and policies to be successful, there must be cooperation between the government-university-industry and community. AFHES project is an important tool to assist SME in the production of foods framed by new health guidelines.